Open innovation in the semiconductor industry: Analysis of Brazilian design houses - Xênia L'amour Campos Oliveira; Maria Elena Leon Olave; Edward David Moreno; Glessia Silva (Innovation & Management Review, 2020)
Purpose - This study aims to understand how Brazilian design houses (DHs) use open innovation in joint development projects for integrated circuits. Design/methodology/approach As a research strategy, qualitative research using multiple case studies was made. As sources of evidence, semi-structured interviews were conducted with three DHs of Programa integrated circuit [circuito integrado(CI)]-Brasil and with four specialists in the field, as well as analysis of documents. The data were analyzed through content analysis. Findings The results showed the DHs use sources of external knowledge in their innovation process, to assist the development of new products, to access new knowledge and skills, to attract financial resources and to be competitive in the market of high technology. Originality/value The study has important implications on the semiconductor industry in Brazil, as the industry is considered strategic for the competitiveness of final goods sector. The importance of encouraging the development of partnerships in the sector, the possibility of using informal agreements to mediate the collaboration between DHs and external agents, and the improvement and long-term continuity of public policies to support the industry are among the implications. In addition to suggestions for new business approaches to assist the strengthening of this segment.
Keywords: 650; Innovation; Microelectronics; Open innovation; Programa CI-Brasil; Semiconductor industry